Childhood cancer registration in Britain: capture-recapture estimates of completeness of ascertainment. - Kroll, M; Murphy, M; Carpenter, L; Stiller, C (2011)
BACKGROUND: Completeness of ascertainment is a very important aspect of cancer registration. There is no recent published estimate for childhood cancer in Britain. METHODS: We estimated completeness of ascertainment by the National Registry of Childhood Tumours for cancer diagnosed under age 15 years in residents of Britain during 2003-04. Stratified two-source capture-recapture was applied to notifications from general cancer registries (CRs) and specialist clinicians. Variation in notification patterns was assessed by logistic regression. Results were verified by cross-checking with Hospital Episode Statistics for leukaemia patients from England born in 1998 and diagnosed before 2005. RESULTS: CRs notified 92-96% of registrations, and specialist clinicians 93%. Notification patterns varied slightly according to registry region, age at diagnosis, diagnostic group, socioeconomic status, and whether the patient had died. Irrespective of stratification by these factors, the overall completeness estimate was 99-100% (assuming independence of sources). Estimated completeness was at least 99% within all subgroups, except for one region (Thames 98-99%) and two small diagnostic groups (germ-cell and gonadal cancer 98-99%, melanoma and non-skin cancer 97-98%). INTERPRETATION: The independence assumption cannot be fully justified, as both sources used records from treatment centres. With this caveat, ascertainment of recently diagnosed childhood cancer in Britain appears to be virtually complete.